2021
DOI: 10.1021/acsmedchemlett.1c00526
|View full text |Cite
|
Sign up to set email alerts
|

Inactivators of Ornithine Aminotransferase for the Treatment of Hepatocellular Carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the second or third leading cause of cancer mortality worldwide (depending on which statistics are used), yet there is no effective treatment. Currently, there are nine FDA-approved drugs for HCC, five monoclonal antibodies and four tyrosine kinase inhibitors. Ornithine aminotransferase (OAT) has been validated as a target in preclinical studies, which demonstrates that it is a potential target to treat HCC. Currently, there are no OAT inactivators in clinical trials for HCC. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…OAT methylation also correlated with numbers of pathways confirmed with tumor‐promoting effect 26 including focal adhesion, ECM receptor, MAPK, Wnt, and PI3K/AKT. Although it is only reported that upregulation of Wnt/β‐catenin pathway correlated with increased OAT expression promoted HCC progression and targeting OAT provided the potential for treatment of HCC, 15 this finding suggests a highlighted correlation of OAT methylation to cancer progression. Moreover, we investigated hypermethylated OAT was most prominently associated with increased sulfur metabolism.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…OAT methylation also correlated with numbers of pathways confirmed with tumor‐promoting effect 26 including focal adhesion, ECM receptor, MAPK, Wnt, and PI3K/AKT. Although it is only reported that upregulation of Wnt/β‐catenin pathway correlated with increased OAT expression promoted HCC progression and targeting OAT provided the potential for treatment of HCC, 15 this finding suggests a highlighted correlation of OAT methylation to cancer progression. Moreover, we investigated hypermethylated OAT was most prominently associated with increased sulfur metabolism.…”
Section: Discussionmentioning
confidence: 95%
“…7 In this study, we attempted to figure out the differential DNA methylation in OSCC compared to normal tissues and found only OAT (from top 20) methylation was significantly associated with the overall survival of OSCC patients. OAT is well known as a mitochondrial enzyme, which is essential for hepatocellular carcinoma (HCC) cells growth, 15 shedding light on the underlying interplay of OAT in cancer progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that OAT was a potential chemotherapy target for cancers. Silverman et al 14 have recently synthesized…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that OAT was a potential chemotherapy target for cancers. Silverman et al 14 have recently synthesized OAT inactivators to inhibit the activity of OAT and lead to downregulation of l ‐Gln and growth inhibition of hepatocellular carcinoma through targeting the Wnt/β‐catenin pathway, which suggests that OAT was an important chemotherapy target for treatment of cancer. Zhu et al 15 recently showed that both human OAT and γ‐aminobutyric acid aminotransferase have a similar active site.…”
Section: Discussionmentioning
confidence: 99%